A conceptual schema for government purchasing arrangements for Australian alcohol and other drug treatment. (September 2016) - Ritter, Alison; Hull, Philip; Berends, Lynda; Chalmers, Jenny; Lancaster, Kari
Abstract: Aim: The aim of this study was to establish a conceptual schema for government purchasing of alcohol and other drug treatment in Australia which could encompass the diversity and variety in purchasing arrangements, and facilitate better decision-maker by purchasers. There is a limited evidence base on purchasing arrangements in alcohol and drug treatment despite the clear impact of purchasing arrangements on both treatment processes and treatment outcomes. Methods: The relevant health and social welfare literature on purchasing arrangements was reviewed; data were collected from Australian purchasers and providers of treatment giving detailed descriptions of the array of purchasing arrangements. Combined analysis of the literature and the Australian purchasing data resulted in a draft schema which was then reviewed by an expert committee and subsequently finalised. Results: The conceptual schema presented here was purpose-built for alcohol and other drug treatment, with its overlap between health and social welfare services. It has three dimensions: 1. The ways in which providers are chosen; 2. The ways in which services are paid for; and 3. How price is managed. Distinguishing between the methods for choosing providers (such as competitive or individually negotiated processes) from the way in which organisations are paid for their provision of treatment (such as via a block grant or payment for activity) provides conceptual clarity and enables closer analysis of each mechanism. Conclusions: Governments can improve health and wellbeing by making informed decisions about the way they purchase and fund alcohol and other drug treatment. Research comparing different purchasing arrangements can provide a vital evidence-base to inform funders; however a first step is to accurately and consistently categorise current approaches against a typology or conceptual schema. Highlights: We need a better understanding of the variety of purchasing arrangements for alcohol and other drug treatment. This study provides a conceptual schema for purchasing arrangements, purpose-built for alcohol and other drug treatment. The schema has 3 dimensions: 1. The ways in which providers are chosen; 2. The ways in which services are paid for; and 3. How price is managed. While empirical comparisons between mechanisms are currently lacking, there is evidence that payment-for-outcomes has not proved effective. Treatment purchasers can use the schema to make more informed decisions about mechanisms. Researchers can use the schema to characterise and compare different purchasing arrangements.